2017
DOI: 10.54386/jam.v19i1.749
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts vis-a-vis productivity of soybean in vertisol of Madhya Pradesh

Abstract: The impact of climate change on agricultural crops is a major concern and threats to the global food security. It also limits the potential of crops and cropping system in a given area. Therefore, the present study was aimed to assess the combined effect of positive (CO2 fertilization, lesser temperature and higher rainfall) and negative (higher temperature, lower rainfall) impacts of the futuristic climatic scenarios on productivity of soybean using APSIM (Agricultural Production Systems sIMulator) model. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Similarly, in the case of pulses, fluctuating temperature and disproportionate rainfall affected pulse productivity though the per capita income from agriculture has had a positive impact on the yield of pulses. Certain studies have forecast that the continuation of certain (climate change) scenarios can reduce crop yield by 40 to 45 percent in the future (Mohanty et al, 2017 ; Dupare et al, 2020 ). For oilseed crops, fluctuation in precipitation along with an increase in rabi (post-rainy season) temperature and an increase in CO 2 emission posed a negative impact on oilseed productivity by reducing the yield up to a certain extent while cropping intensity, fertilizer consumption, use of agricultural machinery and per capita agricultural income affected the yield of oilseeds in a positive rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the case of pulses, fluctuating temperature and disproportionate rainfall affected pulse productivity though the per capita income from agriculture has had a positive impact on the yield of pulses. Certain studies have forecast that the continuation of certain (climate change) scenarios can reduce crop yield by 40 to 45 percent in the future (Mohanty et al, 2017 ; Dupare et al, 2020 ). For oilseed crops, fluctuation in precipitation along with an increase in rabi (post-rainy season) temperature and an increase in CO 2 emission posed a negative impact on oilseed productivity by reducing the yield up to a certain extent while cropping intensity, fertilizer consumption, use of agricultural machinery and per capita agricultural income affected the yield of oilseeds in a positive rate.…”
Section: Resultsmentioning
confidence: 99%
“…Certain studies have forecast that the continuation of certain (climate change) scenarios can reduce crop yield by 40 to 45 percent in the future (Mohanty et al, 2017;Dupare et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…Evaluation of climate change impact on maize yield under different N management strategies revealed that there was more reduction in yield under RCP 8.5 compared to RCP 4.5. Maize yields in sub-tropical climate of Central India in future could be improved by 3t ha -1 by providing optimum dates of sowing and good management practices [62].…”
Section: Biomass Production Of Pigeonpea and Maizementioning
confidence: 99%
“…Hence, it is necessary to exploit th e tec hn olog ies fo r in -s itu mo isture conservation like tillage, land configurations, mulching etc. (Rajput et al, 2009 andMohanty et al, 2017).…”
Section: Introductionmentioning
confidence: 99%